Limiting absorption principle and radiation conditions for Schrödinger operators with long-range potentials - Larsen, Martin Dam (MATHEMATICA SCANDINAVICA, 2024)
We show Rellich’s theorem, the limiting absorption principle, and a Sommerfeld uniqueness result for a wide class of one-body Schrödinger operators with long-range potentials, extending and refining previously known results. Our general method is based on elementary commutator estimates, largely following the scheme developed recently by Ito and Skibsted.